A STUDY ON KURDISH STUDENTS’ ATTITUDES TO GROUP WORK IN THE EFL CLASSROOM - Othman, Hozan Gorgeen; Murad, Ivan Hasan (European Scientific Journal, ESJ, 2015)
Throughout the last two or three decades, group work has become a part that cannot be separated from other classroom activities. This research study identifies the different opinions of Kurdish students concerning the advantages and disadvantages of group work in the classroom. The research was conducted on 100 Kurdish university students who had at least two years experience of group work at Universities in Kurdistan (Zakho, Dohuk, Salahaddin, and Sulaimani universities). Anonymously, a questionnaire was completed and its results were submitted by the respondents, hoping that their responses could directly address the research aim. Then, 20 students from the ones who participated in filling in the questionnaire were chosen and interviewed so as to gain as valid and reliable data as possible for the results of the study to be authentic. Thus, a triangulation methodological strategy was followed in this research study to produce valid results. The findings from both instruments revealed that “better communication”, “group work is a mutual interest”, “group members clarify difficult things to each other” and ’’it takes a short time to finish a task in group work’’ were students’ positive opinions, while “some members prefer to relax and stay silent”, “some members do not like to work”, ’’group work is a waste of time as students talk about external things and they cannot reach any agreement’ ’and “students depend on each other” were their negative opinions concerning group work. Suggesting further considerable studies on attitudes of students concerning group work, the research concludes.